Ontology Development for Knowledge Representation of a Metrology Lab - Luque-Morales, Ramon Alberto; Hernandez-Uribe, Oscar; Mora-Alvarez, Zaida Antonieta; Cardenas-Robledo, Leonor Adriana (Engineering, Technology & Applied Science Research, 2023)
Digital transformation in metrology is impacting the industry, where accurate and fair data are essential to take enterprises to the next level in the digital era. The amount and complexity of information are growing exponentially, and expert knowledge becomes imperative for users to perform measurement tasks and decision-making. This study presents the development of a modular metrological inspection ontology for a metrology laboratory based on the reuse of ontologies related to sensors and units of measurement. Such an ontology considers information about operators and customers (name, telephone number, email) and the linkage to service orders, pieces (length, height, width), measurement strategies (expert notes about measurement procedures and paths), and measuring machines (measuring scope, uncertainty, sensor probe). The proposed solution delivers a digitalized catalog that allows the user to filter records according to the geometrical characteristics of the pieces and recover notes related to measurement procedures and paths for similar cases. The purpose is to promote knowledge sharing and narrow the gap to achieve digital transformation toward Metrology 4.0 in laboratories prepared to offer metrological support.